EFFECT OF CO, CR AND AL ON SPIRULINA PLATENSIS (GOMONT) GEITLER - O. MURALI; SANTOSH KUMAR MEHAR (International Journal of Pharma and Bio Sciences, 2016)
Heavy metal pollution is one of the major environmental problems that the world is facing today. Removal of heavy metals from the contaminated water bodies is a technical challenge which is economically costly also. Use of microorganisms is being considered as one of the cost effective approach to remove the heavy metals from the contaminated water bodies. However, there are many issues related with that and the effect of the heavy metal on the physiology of the microorganism used in the process of bioremediation is one of them. In the present study, an assessment was made of the effect of the heavy metal on the protein composition of Spirulina platensis when it is exposed to different concentrations of the different heavy metal. In the study three different heavy metals viz., Cobalt, Chromium and Aluminium were used both alone in combinations of two different heavy metals to assess their effect on the protein composition of S. platensis by SDS-PAGE electrophoresis. The results indicate that the concentration and the combination of heavy metals has distinct effect on the protein composition of S. platensis, and the effect can be distinguished as the change caused by the exposure to a single heavy metal and that induced by a combination of two different heavy metals.